2015
DOI: 10.1016/j.neuron.2015.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Different Functional Neural Substrates for Good and Poor Language Outcome in Autism

Abstract: Summary Autism (ASD) is vastly heterogeneous, particularly in early language development. While ASD language trajectories in the first years of life are highly unstable, by early childhood these trajectories stabilize and are predictive of longer-term outcome. Early neural substrates that predict/precede such outcomes are largely unknown but could have considerable translational and clinical impact. Pre-diagnosis fMRI response to speech in ASD toddlers with relatively good language outcome was highly similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
200
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(227 citation statements)
references
References 58 publications
16
200
3
1
Order By: Relevance
“…A recent study of ASD outcomes by Lombardo et al (25) corroborates this claim. The authors showed that fMRI data collected during an auditory language task on infants and toddlers, who later developed ASD, predicted a categorical language outcome 1 y postscan [68% accuracy, area under the curve (AUC), 69%].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…A recent study of ASD outcomes by Lombardo et al (25) corroborates this claim. The authors showed that fMRI data collected during an auditory language task on infants and toddlers, who later developed ASD, predicted a categorical language outcome 1 y postscan [68% accuracy, area under the curve (AUC), 69%].…”
Section: Discussionmentioning
confidence: 77%
“…Hearteningly, however, there is evidence that some of these regions may be predictive of other outcomes in ASD populations. The study by Lombardo et al (25) of prospective language outcomes in ASD also showed that activity in the anterior insula and anterior cingulate of the SN, as well as medial prefrontal cortex and portions of the superior temporal cortex included in the DMN, correlated with future language ability using partial least squares correlation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In turn, neuroanatomical, neurochemical, and neurophysiological events occurring in cortical and subcortical brain areas trigger and determine the person’s ability to understand the meaning behind pragmatic aspects of communication. Such skills include the decoding of facial expressions, the appropriate use of eye contact, and joint attention [12, 13]. Data suggest that the infant’s attention to a person’s face is mediated by the subcortical area of the visual neural pathway (e.g., from the retina to the occipital lobe) [11, 14].…”
Section: Introductionmentioning
confidence: 99%
“…*The views expressed in this article are the personal views of the author and may not be understood nor quoted as being made on behalf of or reflecting the position of the European Medicines Agency (EMA) or one of its committees or working parties or any of the national agencies. of brain structure 8 and function 9 and relate them to clinical outcome. Neuroimaging techniques also help us to identify the mecha nisms through which interventions improve functioning.…”
Section: Biomarker Stratification Approachesmentioning
confidence: 99%